Implementasi Pendidikan Agama Islam Dalam Meningkatkan Pemahaman Agama - Ismi Izzatul Shoumi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Islamic religious education is very much needed by the Islamic community today to add insight in understanding religion, because in fact there are still many people who lack understanding of religion, lack of understanding of religion will greatly affect a person in carrying out daily worship and activities related to religion. In the context of fostering religious education in the community, efforts can be made through regular recitations, one of which is found at the Al-Muchlisin taklim assembly. With this taklim assembly, it will help the community in increasing religious understanding and can foster society towards an Islamic society in accordance with the teachings of Islam. So it is deemed necessary for researchers to conduct a research in the form of a thesis with the title